Clinicopathological and molecular features of sessile serrated adenomas with dysplasia or carcinoma. Issue 1 (15th October 2015) - Bettington, Mark; Walker, Neal; Rosty, Christophe; Brown, Ian; Clouston, Andrew; McKeone, Diane; Pearson, Sally-Ann; Leggett, Barbara; Whitehall, Vicki
Abstract : Objective: Sessile serrated adenomas (SSAs) are the precursors of at least 15% of colorectal carcinomas, but their biology is incompletely understood. We performed a clinicopathological and molecular analysis of a large number of the rarely observed SSAs with dysplasia/carcinoma to better define their features and the pathways by which they progress to carcinoma. Design: A cross-sectional analysis of 137 SSAs containing regions of dysplasia/carcinoma prospectively collected at a community GI pathology practice was conducted. Samples were examined for BRAF and KRAS mutations, the CpG island methylator phenotype (CIMP) and immunostained for MLH1, p53, p16, β-catenin and 0-6-methylguanine DNA methyltransferase (MGMT). Results: The median polyp size was 9 mm and 86.5% were proximal. Most were BRAF mutated (92.7%) and 94.0% showed CIMP. Mismatch repair deficiency, evidenced by loss of MLH1 (74.5%) is associated with older age (76.7 versus 71.0; p<0.0029), female gender (70% versus 36%; p<0.0008), proximal location (91% versus 72%; p<0.02), CIMP (98% versus 80%; p<0.02) and lack of aberrant p53 (7% versus 34%; p<0.001) when compared with the mismatch repair-proficient cases. Loss of p16 (43.1%) and gain of nuclear β-catenin (55.5%) were common in areas of dysplasia/cancer, irrespective of mismatch repair status. Conclusions: SSAs containing dysplasia/carcinoma are predominantly small (<10 mm) and proximal. The mismatch repair status separates these lesions into distinct clinicopathological subgroups, although WNT activation and p16 silencing are common to both. Cases with dysplasia occur at a similar age to cases with carcinoma. This, together with the rarity of these 'caught in the act' lesions, suggests a rapid transition to malignancy following a long dwell time as an SSA without dysplasia.